IMMU-23. A NOVEL MASS CYTOMETRY-BASED MULTI-PARAMETER CHARACTERIZATION OF NEOANTIGEN-REACTIVE CD8+ T-CELLS IN PATIENTS PARTICIPATING IN PNOC007 H3.3K27M PEPTIDE VACCINE CLINICAL TRIAL. (4th December 2020) - Taitt, Jared; Nejo, Takahide; Watchmaker, Payal; Almeida, Neil; Okada, Kaori; Shahin, Maryam; Gilbert, Ryan; Molinaro, Annette; Prados, Michael; Mueller, Sabine; Okada, Hideho
Abstract: BACKGROUND: We have identified an HLA-A*02:01-restricted neoantigen epitope encompassing the H3.3K27M mutation and implemented a multi-center clinical trial of the peptide vaccine through the Pacific Pediatric Neuro-Oncology Consortium (PNOC007) for patients with diffuse midline glioma (DMG), including diffuse intrinsic pontine glioma (DIPG). We sought to characterize vaccine-reactive CD8+T-cells subpopulations using their precise activation and developmental status to find their associations with clinical outcomes. METHODS: Mass cytometry (CyTOF) analysis was performed on patient-derived peripheral blood mononuclear cells collected at baseline as well as pre-specified time points throughout the study. Each cell subtype was characterized via tSNE-clustering based on their expression profiles and quantified as a fraction of total CD45+cells. H3.3K27M-reactive CD8+T-cells were evaluated using an H3.3K27M-HLA-A2 dextramer along with a panel of T-cell and myeloid markers. RESULTS: Among all 29 patients enrolled, we analyzed samples from all 19 DIPG and 9 of 10 non-brainstem DMG cases, of which 18 had longitudinal samples available (range: 2–5). Utilizing a novel CyTOF-based immuno-monitoring platform, the expansion of H3.3K27M-reactive CD8+T-cells, defined as a 25% increase at any time-point relative to baseline, was observed in 7 of these 18 patients. Survival analyses indicated that the expansion of H3.3K27M-reactive CD8+T-cells, particularly the effector-memory phenotype, positively correlated with longer overall survival (OS) (median: 16.1 vs 9.7 months, p=0.03), whereas an abundance of early and monocytic myeloid-derived suppressor cells at baseline correlated with shorter OS among DIPG patients (9.5 vs 14.3 months, p=0.002). CONCLUSION: Our novel immuno-monitoring approach offers insight into how vaccine-induced immune responses impact clinical outcomes.